IFNL4 ss469415590 polymorphism is associated with unfavourable clinical and immunological status in HIV-infected individuals. (March 2015) - Machmach, K.; Abad-Molina, C.; Romero-Sánchez, M.C.; Dominguez-Molina, B.; Moyano, M.; Rodriguez, M.M.; Rafii-El-Idrissi Benhnia, M.; Jimenez-Mejias, M.E.; Vidal, F.; Muñoz-Fernández, M.A.; Genebat, M.; Viciana, P.; et al.
Abstract: The IFNL4 ss469415590 polymorphism, in high linkage disequilibrium with the IL28B rs12979860 variant, has been associated with hepatitis C virus clearance. We evaluated whether ss469415590 is associated with clinical and immunovirological parameters in human immunodeficiency virus-infected subjects. We found an independent association of the IFNL4 ss469415590 polymorphism with higher prevalence of AIDS-defining illnesses and lower CD4 T cell numbers. These results suggest the existence of common host defence mechanisms against different viral infections.